2016
DOI: 10.1093/cid/ciw463
|View full text |Cite
|
Sign up to set email alerts
|

Early Response in Cellulitis: A Prospective Study of Dynamics and Predictors

Abstract: In this prospective study of cellulitis, several nonpharmacological factors were associated with lack of early response. Such early nonresponse was rarely related to inappropriate therapy but strongly predictive of early treatment escalation, suggesting that broadening antibiotic treatment often may be premature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 35 publications
5
30
0
3
Order By: Relevance
“…Assessing treatment response at this earlier time point may increase the reliability of the measurement of drug effect, because the outcome is not confounded by natural improvement of disease. 23 Moreover, this end point is in line with the 2013 FDA guidance recommending early clinical response as the primary outcome. 12 Patient-focused outcomes such as patient-reported pain, treatment satisfaction and quality of life were rarely reported.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Assessing treatment response at this earlier time point may increase the reliability of the measurement of drug effect, because the outcome is not confounded by natural improvement of disease. 23 Moreover, this end point is in line with the 2013 FDA guidance recommending early clinical response as the primary outcome. 12 Patient-focused outcomes such as patient-reported pain, treatment satisfaction and quality of life were rarely reported.…”
Section: Discussionsupporting
confidence: 55%
“…Some of the more recent trials used ‘early clinical response’ as the primary outcome, defined as the cessation of lesion spread (measured as the length × width of lesion) 48–72 h after treatment initiation. Assessing treatment response at this earlier time point may increase the reliability of the measurement of drug effect, because the outcome is not confounded by natural improvement of disease . Moreover, this end point is in line with the 2013 FDA guidance recommending early clinical response as the primary outcome…”
Section: Discussionmentioning
confidence: 57%
“…This finding is in contrast to a recent study that found longer duration of symptoms was among the factors related to early response (at day 3). However, the investigation evaluated antibiotic response at day 3 among hospitalized SSTI patients; therefore, may not necessarily be associated with long-term outcomes including post-treatment failure and recurrence that were evaluated in the current study [7]. Importantly, this finding further supports the proposition that time to effective treatment is essential in the management of SSTIs, and possibly, that patients presenting with longer duration (≥7 days) of infections may require more aggressive measures and/or follow-up monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…SSTIs due to CA-MRSA have been implicated to have more serious outcomes compared to community-associated methicillin susceptible S. aureus (CA-MSSA) SSTIs; however, there are limited studies evaluating the differences in treatment outcomes in the primary care setting. Furthermore, while there has been a growing body supporting the assessment of early response in treatment failure among hospitalized patients with SSTIs, very little information is available for outpatients [7, 8]. Tools to better identify those who are at higher risk of experiencing treatment failure are needed to better inform treatment decisions in the outpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“…bd = twice daily; PO = oral; IV = intravenous; qds = four times daily CME Infectious diseases first 3 days of therapy) did not result in improved outcomes and addressing non-antibiotic factors such as limb elevation and treatment of comorbidities should be considered as an integrated part of the clinical management of cellulitis. 23 Outpatient parenteral antimicrobial therapy has become an increasingly important means of delivering ambulatory care. Cellulitis was the most common primary infective diagnosis in UK OPAT Outcomes registry in 2015.…”
mentioning
confidence: 99%